RANCANG BANGUN APLIKASI RADIO STREAMING DENGAN MENGGUNAKAN SHOUTCAST DISTRIBUTED NETWORK AUDIO SERVER (DNAS) - Alauddin Al Ayubi; Didik Kurniawan; Febi Eka Febriansyah (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2016)
Radio Streaming is use technology for sending an audio file simultaneously on multiple computers on a network by using a small data packets and generates output semi-real time. In the process of streaming, a music file will sound when the computer starts receiving the music file data. Shoutcast DNAS is a freeware that is used for streaming radio technology. Shoutcast help the user to provide an Internet Radio Private servers using software that has been provided. Winamp is a multimedia player device created by Nullsoft. The trial results of this study are the Application Streaming Radio can help the user to display the program content of radio, play and lay Radio Streaming and display e-mail addresses, website streaming and also Encoder used affects the occurrence of delay, the connection is unstable causing disconnection in automatic, processor speed and also the speed of the internet connection affects the buffering of streaming player or players.Â Keywords: Streaming Radio, Shoutcast DNAS, Winamp, Encoder.